Management structure, goals and policies for collective bargaining - Leap, Terry 1948- (1995)
This article turns its attention to management, opening with the basic goals and strategies of the management. Differences between unionized and non-unionized firms are explored. The author describes strategies for balancing power between unions and management, and for creating cooperative efforts between union and management.
Introduction -- Management goals and strategies -- the personnel/human resource management function -- Major differences between unionized and nonunionized firms -- Management bargaining goals -- Balancing management and union power structures -- Multi-employer bargaining -- Union-management cooperative efforts -- Summary and conclusions.
Photocopy.
Source: Leap, Terry. Collective Bargaining and Labor Relations. Chapter 7. 2nd ed. [New Jersey] : Prentice Hall, c1995.
Includes bibliographical references (p. 257-260)
Keywords: Industrial relations